Wasiat Penggunaan Tubuh Manusia sebagai Bahan Penelitian dalam Perspektif hukum Islam - M. Iyat; Khaerul Aqbar; Syandri, Syandri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study examines the will for the use of the human body as research material from the perspective of Islamic law. The primary objective is to analyze the provisions of Islamic law regarding the will for the use of the human body for research, which underpins the acceptance or rejection of the use of the human body in research. The research methodology includes literature review and content analysis from Islamic legal sources, with a normative and philosophical juridical approach. The research problems addressed in this study encompass two main topics: first, the concept and basic principles of wills in Islam; and second, the Islamic legal perspective on the practice of using the human body as research material. The results of the study show that Islamic law emphasizes the importance of respecting an individual's will or consent before death in the context of scientific research. The will for the use of the human body for research can be analyzed based on five categories of taklifi law. If the will meets all sharia requirements, it can be categorized as a recommended will. The contribution of this study to the discipline is the affirmation that the balance between scientific advancement and respect for religious values must always be maintained. This study also highlights the relevance of sharia principles in modern medical research ethics, especially in life-threatening situations, and the importance of scientific transparency and responsibility to avoid exploitation.